Effect of Intravenous IgM-Enriched Immunoglobulins on Presepsin and Other Sepsis Biomarkers - Scarpati, Giuliana; Baldassarre, Daniela; Tripepi, Giovanni; Boffardi, Massimo; Piazza, Ornella (Frontiers in Pharmacology, 2021)
Patients in septic shock with low IgG and IgM serum concentrations have higher mortality rates compared to those with normal immunoglobulin levels and, therefore, there is a rational explanation to administer intravenous IgM-enriched immunoglobulins to septic patients in ICU. Aim of this study is to evaluate the effectiveness of intravenous IgM-enriched immunoglobulins in decreasing several sepsis biomarker concentrations. 26 sepsis patients were enrolled in this observational cohort study and Nitric Oxide, Endocan, Pentraxin and presepsin serum levels were measured during their first 3 days of ICU stay. The use of intravenous IgM-enriched immunoglobulins did not influence the temporal evolution of SOFA, Nitric Oxide, Endocan, Pentraxin and presepsin in the first 3 days of ICU stay in a statistically significant manner, even if Presepsin decreased of 25% from day 1 to day 2 in the Pentaglobin group. It seems possible that Pentaglobin infusion reduces the presepsin level in a more effective way if it were administered to a younger population (p=0.012). In conclusion, age modifies the response of Presepsin to Pentaglobin and is a critical variable when investigating the effect of intravenous IgM-enriched immunoglobulins on sepsis.